2004
DOI: 10.1002/bit.20168
|View full text |Cite
|
Sign up to set email alerts
|

Bone repair with a form of BMP-2 engineered for incorporation into fibrin cell ingrowth matrices

Abstract: Most growth factors naturally involved in development and regeneration demonstrate strong binding to the extracellular matrix and are retained there until being locally mobilized by cells. In spite of this feedback between cell activity and growth factor mobilization in the extracellular matrix, this approach has not been extensively explored in therapeutic situations. We present an engineered bone morphogenetic protein-2 (BMP-2) fusion protein that mimics such function in a surgically relevant matrix, fibrin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(124 citation statements)
references
References 50 publications
0
121
0
3
Order By: Relevance
“…The Hubbell group has turned their attention to designing and synthesizing hydrogels that mimic the bi-directional biomolecular interactions that naturally occur between cells and the extracellular matrix (ECM) surrounding them [184,[273][274][275][276][277][278][279][280][281][282][283][284][285]. They have found that signals such as cell adhesion sites, bound growth factors, and cleavage sites for proteolytic activity are essential for cells to be able to remodel the ECM and sustain tissue regeneration.…”
Section: Enzymatically Cleavable Peptide-based Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Hubbell group has turned their attention to designing and synthesizing hydrogels that mimic the bi-directional biomolecular interactions that naturally occur between cells and the extracellular matrix (ECM) surrounding them [184,[273][274][275][276][277][278][279][280][281][282][283][284][285]. They have found that signals such as cell adhesion sites, bound growth factors, and cleavage sites for proteolytic activity are essential for cells to be able to remodel the ECM and sustain tissue regeneration.…”
Section: Enzymatically Cleavable Peptide-based Hydrogelsmentioning
confidence: 99%
“…To impart these additional functionalities to artifical ECMs, peptides are covalently incorporated into one of two types of chemically crosslinked hydrogels. The first class of hydrogels is based on naturally occurring fibrin, which is spontaneously formed by the polymerization of fibrinogen in the presence of thrombin and further cross-linked by the transglutaminase activity of factor XIIIa [273][274][275][276][277][278]. Ehrbar et al engineered a vascular endothelial growth factor (VEGF) fusion protein that includes a substrate for binding to the fibrin matrix by transglutaminase during polymerization as well as a plasmin cleavage site for invading cells to release the bound growth factor [276].…”
Section: Enzymatically Cleavable Peptide-based Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach is to chemically modify titanium prostheses or other materials, if necessary including reactive groups that are able to bind growth factors and to release them slowly. We and others could show that such an approach is able to induce biological activity in model cell lines and in vivo as well, see, e. g. [7,8]. Despite many successful efforts to solve the problem of long-term delivery by strategies like the one just discussed many researchers may prefer gene-therapeutic strategies (cf.…”
Section: Towards Future Innovative Strategies: Animal Modelsmentioning
confidence: 99%
“…Furthermore, coupling oligopeptides that contain the RGD sequence to protein delivery vehicles may also improve the cellular response to growth factors by facilitating cell migration into the material, activating the cells to the desired responsive state and subsequently exposing the cells to the drug in a controlled manner 84 . For example, binding BMP2 to fibrin gels has stimulated the growth of bone into gels in several animal models 85 . In a similar manner, binding of VEGF and RGD-containing oligopeptides to synthetic hydrogels have also stimulated vascularization of the gels 86 .…”
Section: Antisense Therapymentioning
confidence: 99%